A Revision of the Pseudotropheus elongatus species group (Teleostei: Cichlidae) With Description of a New Genus and Seven New Species - Li, Shan; Konings, Adrianus F.; Stauffer, Jay R., Jr. (Zootaxa, 2016)
Lake Malaŵi is known for its endemic haplochromine species flock, most notably the rock-dwelling cichlids known as mbuna. The group of mbuna referred to as the Pseudotropheus elongatus species group is currently comprised of Metriaclima spp., Tropheops spp., Cynotilapia spp., and Pseudotropheus spp. In this study, Chindongo, a new genus with the type species C. bellicosus, is described for additional species in this group. Chindongo is distinguished from other mbuna genera by 1) the presence of bicuspid teeth in the anterior portion of the outer row of both upper and lower jaw; 2) a moderately to steeply sloped vomer with a narrow rostral tip which makes an angle of between 53° and 68° with the parasphenoid; 3) a small mouth with the lower jaw slightly shorter than the upper; 4) a broad anterior dentigerous area on both premaxilla and dentary with three or more rows of teeth (usually 5–6 rows); 5) a flank melanin pattern consisting of vertical bars without horizontal elements at any stage of development. Chindongo bellicosus is distinguished by its color pattern and shallower body from the other species which we have transferred to Chindongo. We also describe six new elongate mbuna species and place them into three available genera, they include: Metriaclima flavicauda, M. usisyae, Tropheops kumwera, T. biriwera, T. kamtambo, and Cynotilapia chilundu.